KONDISI OPTIMUM PROSES KEMPA PANAS DALAM PEMBUATAN PAPAN PARTIKEL DENGAN PEREKAT KITOSAN (PERENNIAL, 2019)
Shrimp skin contains chitin that is the second largest biopolymer after cellulose. The chitin can be isolated to produce chitosan. Chitosan is a natural adhesive that can be applied in producing particleboards to substitute formaldehyde-based adhesives. The purpose of this study was to analyze the hot-pressing condition in term of temperature and pressing time on the physical and mechanical properties of the particleboards produced by using chitosan as adhesives. The particleboards were made with the size of 25x25x0.7 cm and target density of 0.75 g/cm3. The particleboards were produced using different temperatures (160ºC, 180ºC, and 200ºC) and pressing times (9, 12, and 15 minutes. The results showed that the chitosan produced met the standards, and temperature and compression time had a significant interaction effect on the thickness swelling and modulus of elasticity. The optimum combination of temperature and pressing time is 180ºC and 12 minutes, respectively. The produced boards have the characteristics of moisture content 12.2%, density 0.81, water absorption 84.47%, thickness swelling 19.73%, modulus of rupture 143.36 kg/cm2, modulus of elasticity 23,367.79 kg/cm2, and internal bonding 9.03 kg/cm2.
Keywords: chitosan; particle board; temperature and pressing time; hot press